Achieving Balance between Car Accessibility and good Urban Environment - Svensson, Tomas (Proceedings from the Annual Transport Conference at Aalborg University, 2000)
This paper will discuss some of the results from, and the applied methodology within, the research project “Balancing car accessibility and good urban environment”. The central issue concerns the balance between individual benefit of car-access and the public benefit of a good urban environment. There is no functioning market where this balance can be effectively settled because “urban environment” is an example of a public good that can not be purchased in desired quantities on a traditional market. The isolated behaviour of an individual, or a household, has no impact on the total outcome, which in turn will influence the behaviour in certain directions. The purpose of the study is to investigate and analyse the balance between individual gains offered by unlimited car-access and the following consequences of the total traffic by private cars, that individuals would choose if the connections between these variables were made clear. This research question is answered by letting individuals choose among different scenarios concerning the design of inner cities and residential areas in suburbs, by means of a questionnaire. By letting the individuals express their attitudes towards different parts of the scenarios and answer questions concerning their socio-economic background and travelling behaviour, the analysis is further advanced. The results of the study show that, within the boundaries of the applied methodology, a majority of the individuals prefer scenarios where all kinds of road-users relatively safely coexists on streets and roads in towns and cities, and where this condition has been reached by traffic calming measures. Compared to the present situation this means a rather large reduction in car-traffic and parking in, especially, inner cities with corresponding improvements in safety and assigned capacity for pedestrians and cyclists.